Toward a More Balanced Representation of Disability? A Content Analysis of Disability Coverage in the Flemish Print Media - Goethals, Tina; Mortelmans, Dimitri; Van Hove, Geert (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change, 2018)
Although the relations between media coverage and the public are complex, the media has a powerful influence on the way ‘disability’ as a phenomenon is perceived and on the process of attitude formation. Hence, it is important to document the depiction of people with disabilities and the myths and stereotypes perpetuated by media portrayals of persons with disabilities. This paper reports on a quantitative examination of the extent and nature of the coverage of people with disabilities in the print media in Flanders, the Dutch speaking part of Belgium. Seven newspapers and 16 magazines between January 2003 and December 2012 were content-analysed. Key findings include a sorely limited coverage, or even total lack of representation, in certain media sources. The study also discovered interesting correlations between gender, age and type of magazine on the one hand, and the type of disability on the other. Analysis also revealed that print media focuses on certain disabilities. In addition, the results showed that, looking over the ten-year time span, some events have more influence than others on the evolution of the quantity of coverage. The paper concludes with a discussion of these findings and their implications, from the perspective of disability studies and with reference to Cooley’s concept of the looking glass self. It is argued that media representation of disability reflects certain broader ideologies and socio-political processes shaped by basic exclusionary social frames. Yet, the media do more than hold up a mirror to basic mindsets and frames. As the media functions as mechanisms for strengthening and entrenching the social order, they transmit hegemonic conceptions and play a significant role in the ongoing construction of disability discourses.